2019
DOI: 10.29328/journal.jhcr.1001010
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of varicella zoster virus

Abstract: Varicella zoster virus behaves differently from other herpes viruses as it differs from them in many aspects. Recently, there has been growing evidence on the benefi cial effects of the virus in immune compromised hosts and these effects are translated into prolongation of survival. The reported benefi cial effects of the virus include: (1) stimulation of bone marrow activity in patients with hematologic malignancies and bone marrow failure syndromes, (2) antitumor effects in various hematologic malignancies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 410 publications
(774 reference statements)
0
4
0
Order By: Relevance
“…The putative roles of BM-MSCs during infection are: (1) detection of pathogens, (2) activation of host immune responses, (3) elimination of pathogens, (4) induction of proinflammatory gradients, and (5) modulation of proinflammatory host immune response due to having specific immunoregulatory properties of MSCs including: inhibition of differentiation of monocytes to dendritic cells (DCs), alteration of cytokine profile of DCs, induction of tolerant phenotypes of naïve and effector T-cells, inhibition of antibody production by B-cells, and suppression of natural killer (NK) cell proliferation and NK-mediated cytotoxicity [1,2,28,34]. BM-MSCs may augment antimicrobial responses, abridge proinflammatory and damage responses, and ameliorate associated tissue injury and they appear to function as a critical fulcrum providing balance by promoting pathogen clearance during the initial inflammatory response, and suppressing inflammation to preserve integrity of the host and facilitate tissue repair [1,2,34].…”
Section: Role Of Mscs In Host Defense and Infectionsmentioning
confidence: 99%
“…The putative roles of BM-MSCs during infection are: (1) detection of pathogens, (2) activation of host immune responses, (3) elimination of pathogens, (4) induction of proinflammatory gradients, and (5) modulation of proinflammatory host immune response due to having specific immunoregulatory properties of MSCs including: inhibition of differentiation of monocytes to dendritic cells (DCs), alteration of cytokine profile of DCs, induction of tolerant phenotypes of naïve and effector T-cells, inhibition of antibody production by B-cells, and suppression of natural killer (NK) cell proliferation and NK-mediated cytotoxicity [1,2,28,34]. BM-MSCs may augment antimicrobial responses, abridge proinflammatory and damage responses, and ameliorate associated tissue injury and they appear to function as a critical fulcrum providing balance by promoting pathogen clearance during the initial inflammatory response, and suppressing inflammation to preserve integrity of the host and facilitate tissue repair [1,2,34].…”
Section: Role Of Mscs In Host Defense and Infectionsmentioning
confidence: 99%
“…There is evidence that BM-MSCs have been proposed to be able to present viral antigens as antigenpresenting cells to cytotoxic T (CT) cells. Still, they aren't entirely able to process the viral antigens themselves [15]. Liotta et al reported that when BM-MSCs express the TLR3 and TLR4, their immune-suppressive response is blocked, and the T cell response to double-stranded RNA viruses is restored [16].…”
Section: Tlrs and Msc Interactions In Viral Infectionsmentioning
confidence: 99%
“…(4) MSCs can significantly reduce the pathogenic sings of alveolar fluid clearance caused by influenza A/H5N1 infection in vitro and prohibit or reduce influenza A/H5N1-associated acute lung injury in vivo [13][14][15]. The aim of this mini-review is the gathering and discussion of TLRs-related aspects of MSC therapy in inflammation and, subsequently, viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…The capsid of VZV is a regularly shaped icosahedron consisting of 20 triangular faces and 12 corners. The size of VZV ranges from 150-200 nm, and the envelope contains several glycoproteins that allow the virus to enter sensory nerve cells, where it replicates (7).…”
Section: Introductionmentioning
confidence: 99%